Nanostructured Boron Doped Diamond Electrodes with Increased Reactivity for Solar‐Driven CO2 Reduction in Room Temperature Ionic Liquids. Issue 21 (11th September 2020) - Knittel, Peter; Buchner, Franziska; Hadzifejzovic, Emina; Giese, Christian; Quellmalz, Patricia; Seidel, Robert; Petit, Tristan; Iliev, Boyan; Schubert, Thomas J. S.; Nebel, Christoph E.; Foord, John S.
Abstract: Conductive, boron doped diamond (BDD) is an extraordinary material with many applications in electrochemistry due to its wide potential window, outstanding robustness, low capacitance and resistance to fouling. However, in photoelectrochemistry, BDD usually requires UV light for excitation, which impedes e. g., usage in CO2 to fuel reduction. In this work, a heavily boron doped, nanostructured diamond electrode with enhanced light absorption has been developed. It is manufactured from BDD by reactive ion etching and presents a coral‐like structure with pore diameters in the nanometer range, ensuring a huge surface area. The strong light absorbance of this material is clearly visible from its black color. Consequently, the material is called Diamond Black (DB). Electrochemical and X‐ray photoelectron spectroscopy measurements performed at near‐ambient pressure conditions of water vapor demonstrate increased surface reactivity for the hydrogen‐terminated DB compared to oxidized surfaces. Depending on the surface termination, the wettability and hence the electrochemically accessible area can be changed. Photoelectrochemical conversion of CO2 was demonstrated using a Cu2 O‐modified electrode in ionic liquids under solar illumination. High formic acid production rates at low catalyst deposition times can be obtained paired with an increased catalyst stability on the DB surface. Abstract : A new best friend ? A nanostructured boron doped diamond electrode with a 80‐fold increased surface area is presented that shows higher surface reactivity in electrochemical characterization as well as near‐ambient pressure X‐ray photoelectron spectroscopy. CO2 conversion to liquid products in room temperature ionic liquids with high efficiency and enhanced catalyst stability is obtained using these electrodes modified with Cu2 O.